Zakat and Macro Economic Effects on Indonesian Inflation - Rahmat Fajar; Erike Anggraini; Ahmad Habibi; Heni Noviarita (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to analyze whether there is an effect of zakat, investment, exchange rate, BI rate and government spending on inflation in Indonesia for the 2009-2019 period. The type of data used is secondary data obtained from BPS, BI, Ministry of Trade through published agency reports which are analyzed using multiple linear regression with the help of the E-Views 10 Program. The results of this study are: (1) zakat variables, investment, exchange rates, The BI rate and government spending partially have no effect on inflation in Indonesia for the 2009-2019 period. (2) variables of zakat, investment, exchange rate, BI rate and government spending simultaneously have no effect on inflation in Indonesia for the 2009-2019 period. (3) The concept of inflation in the Islamic view refers to Al-Maqrizi's inflation theory which states that inflation can occur by natural conditions as well as human error and a system that is not transparent and accountable. This increase in inflation can be minimized by the concept of zakat through demand pull inflation, while investment plays a role in suppressing inflation through cost push inflation. On the other hand, macroeconomic variables such as exchange rates, BI Rate and Government Expenditures play a role in controlling inflation by applying the Islamic concept, namely the prohibition of usury, maysir and prioritizing the principle of justice.